2015
DOI: 10.4103/2231-4040.165015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brahmyadi Churna (Brahmi, Shankhapushpi, Jatamansi, Jyotishmati, Vacha, Ashwagandha) and tablet Shilajatu in essential hypertension: An observational study

Abstract: Hypertension (HTN) is one among the fiery health problems of the present era. Since it does not cause symptoms usually for many years until a vital organ is damaged. The present study was carried out on 40 patients of essential HTN with Brahmyadi Churna and tablet Shilajatu for a period of 1 month with milk as Anupana. Observation was done before the treatment, 3 mid test assessments on 7th, 14th, and 21st day, posttest assessment was done on 30th day. Intervention revealed that 19 had marked improvement, 14 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Another study showed that both trivrutadi yoga virechana and Dashamoola kwatha kaala basti with add on A rjunadi Ghana vati had antihypertensive effect and were comparable [54]. Brahmyadi churna [55], Shilajatu [55], Chandramaradi yoga [56] were also effective. Other herbals that showed antihypertensive activity are Allium sativum (Garlic) [57], Zingiber officinale (Ginger) [58], Sarpagandha [59], Cassia occidentalis (Kasamarda) [60], Annona muricata [61], Achillea wilhelmsii C [62] and Coleus forskohlii [63].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that both trivrutadi yoga virechana and Dashamoola kwatha kaala basti with add on A rjunadi Ghana vati had antihypertensive effect and were comparable [54]. Brahmyadi churna [55], Shilajatu [55], Chandramaradi yoga [56] were also effective. Other herbals that showed antihypertensive activity are Allium sativum (Garlic) [57], Zingiber officinale (Ginger) [58], Sarpagandha [59], Cassia occidentalis (Kasamarda) [60], Annona muricata [61], Achillea wilhelmsii C [62] and Coleus forskohlii [63].…”
Section: Discussionmentioning
confidence: 99%